2020
DOI: 10.1177/1747021820921345
|View full text |Cite
|
Sign up to set email alerts
|

Wholist–analytic cognitive styles modulate object-based attentional selection

Abstract: Previous studies have shown that individual difference plays an important role in the object-based cueing effect observed in experiments on attentional selection. A wide range of studies have also used the theory of cognitive style to explain individual strategies in most cognitive processes. However, the characteristics of individuals that modulate object-based attentional selection are still unclear. To investigate the modulation of object-based attention by cognitive style, this study used a classic two-rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 44 publications
2
0
0
Order By: Relevance
“…We found that the modulation of cue validity by different cue position conditions (animate and inanimate) was also confounded with object orientation; this was in accordance with previous studies (e.g., Chen & Cave, 2019; Hein et al, 2017; Hu, Liu, Song et al, 2021; Hu, Liu, Wang et al, 2020), reporting that the object-based effects were confounded with the meridian effect in the two-rectangle paradigm, and they also obtained pure object-based effects by arranging the data by cue–target orientation instead of the object orientation. Therefore, to further explore whether different cue positions modulate the pure object-based effects, we also arranged the data by cue–target orientation, not the object orientation, and conducted a three-way repeated measures ANOVA with cue position cue–target orientation (horizontal and vertical), (animate and inanimate), and cue validity (invalid same-object and invalid different-object) as within-subject factors.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…We found that the modulation of cue validity by different cue position conditions (animate and inanimate) was also confounded with object orientation; this was in accordance with previous studies (e.g., Chen & Cave, 2019; Hein et al, 2017; Hu, Liu, Song et al, 2021; Hu, Liu, Wang et al, 2020), reporting that the object-based effects were confounded with the meridian effect in the two-rectangle paradigm, and they also obtained pure object-based effects by arranging the data by cue–target orientation instead of the object orientation. Therefore, to further explore whether different cue positions modulate the pure object-based effects, we also arranged the data by cue–target orientation, not the object orientation, and conducted a three-way repeated measures ANOVA with cue position cue–target orientation (horizontal and vertical), (animate and inanimate), and cue validity (invalid same-object and invalid different-object) as within-subject factors.…”
Section: Resultssupporting
confidence: 92%
“…The results of Experiment 3 showed that the object-based effects in horizontally oriented objects were larger than those in vertically oriented objects, and this was in accordance with previous studies demonstrating that object orientation can modulate object-based attention (e.g., Hein et al, 2017; Hu, Liu, Song et al, 2021; Hu, Liu, Wang et al, 2020). More importantly, the object-based effects in animate objects were larger than those in inanimate objects, due to faster response to invalid same-object location and slower response to invalid different-object location.…”
Section: Resultssupporting
confidence: 90%